Management of Sewing Training Program in an Effort to Improve the Skills of Trainees at the UPT Vocational Training Center of Pandeglang Regency - Amalia, Mila; Sholih, Sholih; Fauzi, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This inquire about points to depict (1) the administration of sewing Training in making strides the abilities of learners at the UPT Balai Latihan Kerja in Pandeglang Rule, and (2) the change of sewing abilities among learners at the Balai Latihan Kerja in Pandeglang Rule. The inquire about strategy utilized may be a graphic strategy with a subjective approach. The information collection strategies utilized are perception, interviews, documentation and writing considers. The information sources in this inquire about comprise of 8 people: 1 Training organizer, 1 teachers, and 6 sewing learners at the UPT Balai Latihan Kerja in Pandeglang Rule. The investigate comes about appear that: (1) Sewing Training administration comprise of arranging, execution, and assessment; the Training exercises have been carried out ideally, and the assessment of the sewing Training appears noteworthy comes about, as nearly all members have secured business, either in companies or as autonomous business people within the sewing field. (2) The comes about of aptitude change after taking part in this sewing Training are that members pick up modern information and abilities in sewing by utilizing the skill procured and the apparatuses and materials given amid the Training. These serve as the starting capital to gotten to be autonomous business visionaries in the domestic sewing benefit segment, such as sewing clothing for every day needs.